Microscopic study of dental hard tissues in primary teeth with Dentinogenesis Imperfecta Type II: Correlation of 3D imaging using X-ray microtomography and polarising microscopy. Issue 7 (July 2015) - Davis, Graham R.; Fearne, Janice M.; Sabel, Nina; Norén, Jörgen G.
Highlights Teeth affected by dentinogenesis imperfect are investigated with polarised light microscopy and X-ray microtomography. Structures and mineral distributions are studied in three dimensions. Large tubules are seen corresponding to the original location of primary dentine. A network of vessels, or the remnants of vessels, is seen in the location of the original pulp chamber. Even after apparent complete obliteration of the pulp chamber, this network of vessels may provide a pathway for bacterial infection.